Thyroid nodule morphology affects the efficacy of ultrasound-guided interstitial laser ablation: A nested case-control study. (7th October 2014) - Gambelunghe, Giovanni; Bini, Vittorio; Stefanetti, Elisa; Colella, Renato; Monacelli, Massimo; Avenia, Nicola; De Feo, Pierpaolo
Abstract: Purpose : The literature reports a wide range of percentages of ablation in the treatment of thyroid nodules. The aim of this nested case-control study was to evaluate whether the different morphological (well-defined vs. agglomerate) characteristics of nodules affect the success rate. Materials and methods : We selected 20 patients with a single and /or dominant well-defined nodule (group 1) and 20 with a nodular formation resulting from the fusion of multiple nodules (group 2). All the nodules were treated by the laser method receiving the same energy. Results : At 6 months, patients in group 1 showed a greater decrease in volume than those in group 2. These differences were more evident after 12 months. Conclusions : Our study demonstrates that the efficacy of laser treatment can be predicted by nodule morphology and contributes to explaining the wide differences in the percentages of ablation reported in literature.